Gendered Family Violence Among Migrants Seeking International Protection: A Life Course Perspective - Weitzman, Abigail (2023)
Although family and migration scholars recognize that intimate partner violence (IPV) can motivate women's movement between countries, little research considers IPV or other gendered family violence further back in women migrants' life histories or explores the legacy of gendered family violence in cases where such violence is not the primary push factor. Here, we analyze in-depth interviews conducted among 34 Latin American women seeking asylum or international protection from a diversity of threats to comprehensively understand their experiences with childhood and adult family violence prior to migration. Our analysis reveals three key takeaways. First, IPV, incest, abandonment, and other forms of gendered family violence can characterize women's family dynamics across the life course even when these experiences do not directly prompt migration. Second, amidst pervasive patriarchal norms, family violence has the power to destabilize women's social circumstances and fracture their ties to family members in ways that indirectly encourage migration. Third, owing to these same gender norms, even when gendered family violence directly prompts migration, women may conceptualize their primary motive as protecting their children rather than themselves. These findings move beyond common conceptualizations of the family violence-migration nexus and highlight the breadth and implications of gendered family violence among migrants seeking protection from a broad spectrum of intra- and extra-familial threats.